2012
DOI: 10.1007/s10508-012-9921-y
|View full text |Cite
|
Sign up to set email alerts
|

Mostly Heterosexual and Mostly Gay/Lesbian: Evidence for New Sexual Orientation Identities

Abstract: A sample of 1,784 individuals responded to an online survey advertised on the Facebook social networking website. We explored the sexual orientation continuum by focusing on three components: self-reported sexual orientation identity, sexual attraction, and sexual partners. Results supported a 5-category classification of identity (heterosexual, mostly heterosexual, bisexual, mostly gay/lesbian, gay/lesbian) in that two added identity labels (mostly heterosexual and mostly gay/lesbian) were frequently chosen b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
146
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 265 publications
(170 citation statements)
references
References 47 publications
16
146
0
4
Order By: Relevance
“…Still, numbers on these scales are usually used to categorize people. This categorization has been critiqued (e.g., Diamond, 2014;Korchmaros et al, 2013;Vrangalova & Savin-Williams, 2012), with the recognition that individuals with the same''Kinsey number'' may not actually have the same sexualities (Whalen, Geary, & Johnson, 1990). Some studies recruit by sexual identity and then categorize people into specific sexual orientation groups (Jordan- Young, 2010), undermining the point of separating these identity and orientation constructs (Korchmaros et al, 2013).…”
Section: Limitations Of Existing Theories About Sexual Orientationmentioning
confidence: 99%
“…Still, numbers on these scales are usually used to categorize people. This categorization has been critiqued (e.g., Diamond, 2014;Korchmaros et al, 2013;Vrangalova & Savin-Williams, 2012), with the recognition that individuals with the same''Kinsey number'' may not actually have the same sexualities (Whalen, Geary, & Johnson, 1990). Some studies recruit by sexual identity and then categorize people into specific sexual orientation groups (Jordan- Young, 2010), undermining the point of separating these identity and orientation constructs (Korchmaros et al, 2013).…”
Section: Limitations Of Existing Theories About Sexual Orientationmentioning
confidence: 99%
“…[14][15][16][17] The anonymity guaranteed by online surveys are of benefit if study topics are personal or taboo, such as questions on sexuality as in the case of HPV, where household or schoolbased recruitment strategies may be less favorable. 16,17 Recently, a study used Facebook to collect data on knowledge of HPV and cervical cancer among young women in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] The anonymity guaranteed by online surveys are of benefit if study topics are personal or taboo, such as questions on sexuality as in the case of HPV, where household or schoolbased recruitment strategies may be less favorable. 16,17 Recently, a study used Facebook to collect data on knowledge of HPV and cervical cancer among young women in Australia. 18 In that study, characteristics of the study population did not differ from data from the National Bureau of Statistics with regard to geographic region, ethnicity and socioeconomic status; however, women aged 16-17 y and those with higher education were underrepresented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a US nationally representative study, one third of those who were equally, mostly, or only attracted to men identified as mostly gay men (Chandra, Mosher, & Copen, 2011). Another study found mostly gay men were more similar to selfidentified bisexual than gay men in their reports of sexual attraction to and sex partners with both 5 sexes (Vrangalova & Savin-Williams, 2012). Other than these findings, little is known about men with a predominant but not exclusive sexual orientation towards men.…”
Section: Introductionmentioning
confidence: 99%